ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK BERDASARKAN GAYA BELAJAR MODEL HONEY-MUMFORD - Heryani, Yeni; Ramadani, Rika (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2019)
This research is aimed to describe the mathematical problem solving abilities with Polya steps to the high school student grade XI based on Honey-Mumford's learning style. This research was qualitative research with descriptive method. Questionnaires, mathematical problem solving ability test, and interview were used as data collection techniques. The research instruments that used here were researcher, Honey-Mumford model learning style questionnaires (LSQ questionnaire), questions for mathematical problem solving ability test, and interview guidelines. The source of the data for this research were students of class XI IPA at SMA Muhamadiyah Singaparna in the academic year 2018/2019. Data reduction, data presentation, and conclusion drawing were used as the data analysis techniques. The results showed that students with activist learning style were able to take steps to understanding the problem, devising a plan, carring out the plan, and then looking back for the question number 1. Meanwhile, Students with reflector learning style were able to take steps to understanding the problem, devising a plan, carring out the plan, and then looking back for the question number 1, and also able to take steps to understanding the problem and carring out the plan for the steps in mathematical problem solving abilities for question number 2. In the other side, students with pragmatic type of learning style were able to take steps to understanding the problem, devising a plan, carring out the plan, looking back for the question number 1, and then carry out the solution plan for question number 2. Other than that, students with theorist learning style were able to take steps to understanding the problem, devising a plan, carring out the plan, and then looking back for the question number 1